1977
DOI: 10.1007/bf02533310
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of autoxidized fats by gas chromatography‐mass spectrometry: II. Methyl linoleate

Abstract: The gas chromatography-mass spectrometry (GC-MS) approach developed in the preceding paper was applied for qualitative and quantitative investigations of autoxidation products of methyl linoleate. A GC-MS computer summation method was standardized with synthetic 9- and 13-hydroxyoctadecanoate. Equal amounts of 9- and 13-hydroperoxides were found in all samples of linoleate autoxidized at different temperatures and peroxide levels. The results are consistent with the classical free radical mechanism of autoxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(29 citation statements)
references
References 23 publications
2
26
0
1
Order By: Relevance
“…Unsaturated fatty acids are much more susceptible to oxidation than their saturated analogues, especially at elevated temperature. The formation and decomposition of hydroperoxide intermediates is predicted by the number and location of ethylenic bonds (23)(24)(25). We previously found that cholesterol was oxidized in conjunction with the oxidation of coexisting unsaturated fatty acid esters of triacylglycerols (17).…”
Section: Discussionmentioning
confidence: 98%
“…Unsaturated fatty acids are much more susceptible to oxidation than their saturated analogues, especially at elevated temperature. The formation and decomposition of hydroperoxide intermediates is predicted by the number and location of ethylenic bonds (23)(24)(25). We previously found that cholesterol was oxidized in conjunction with the oxidation of coexisting unsaturated fatty acid esters of triacylglycerols (17).…”
Section: Discussionmentioning
confidence: 98%
“…One mole of linoleic acid reacts with 1 mol of oxygen and forms the hydroperoxide [16] and this reaction changes non-conjugated diene of linoleic acid to conjugated diene [17], which can be determined by the POV test and the absorbance at 233 nm. Figure 1 shows that the changes in the POV, UV absorbance, and HMB, TBA, and CV values.…”
Section: Correlation Among 5 Tests For the Determination Of Peroxidesmentioning
confidence: 99%
“…It is well known that the free radical peroxidation of methyl linoleate produces four conjugated regio-geometric isomers: the 9-and 13-perhydroxy cis, trans (c,t) and trans,trans (t,t) isomers (30,31). In contrast, singlet oxygen oxidation of methyl linoleate yields both conjugated and nonconjugated isomers in approximately equal amounts (32,33), presumably by the concerted ene reaction with singlet oxygen, rather than via a peroxyl radical intermediate.…”
Section: Resultsmentioning
confidence: 91%